Epistemologi Pendidikan Islam: Memutus Dominasi Barat terhadap Pendidikan Islam - Makki Makki (Madrasah Tsanawiyah DDI Cilellang, 2019)
This study discusses the essence, approach, and method of the epistemology of Islamic education and its urgency to developing Islamic education in the modern era. The discussion will clarify the reasons why Western education dominates and influences Islamic education, the epistemological system of the Islamic education, the renewal of the epistemology of the Islamic education, and efforts to build the epistemology of the Islamic education. This research is a conceptual study whose data is collected through library documentation and analyzed by content analysis method. The results show that 1) the epistemology of the Islamic education is a series of ways to find the theories and concepts of Islamic education, so as to solve various problems of Islamic education; 2) there are four epistemological approaches to the Islamic education: empirical, scientific, philosophical, and religious (theological). There are six epistemological methods of Islamic education, namely: rational, intuitive, dialogical, comparative, critical, and ‘ibrah; 3) the urgency of the epistemology of Islamic education in developing Islamic education in the modern era is to filter Western thought or shield from the influence of Western epistemology, reform Islamic education without removing idealism (characteristic of Islam), integration of Islamic education with the national education system.